2007
DOI: 10.1177/1082013207078066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Dry- and Moist-Heating Treatments on the Biochemical Characteristics of Terminalia catappa L. Seed

Abstract: The effects of dry- (roasting) and moist-heat (boiling) treatments on the biochemical characteristics of Terminalia catappa (tropical almond) seed were determined. There were no significant differences in crude protein, fat, ash, and carbohydrate content of the seeds with respect to processing. Boiling increased significantly ( P < 0.05) the crude fibre, however roasting reduced it. Roasting had a better effect on the total dietary fibre (TDF) and gross energy level of the seeds than boiling. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This can be supported by the publications of Oliveira et al (2000), Ezeokonkwo (2007), Biego et al (2012), Monnet et al (2012) and Atsu Barku et al (2012). Ezeokonkwo and Dodson (2004) reported that the seed has essential amino acids that can support growth and a high dietary protein quality.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…This can be supported by the publications of Oliveira et al (2000), Ezeokonkwo (2007), Biego et al (2012), Monnet et al (2012) and Atsu Barku et al (2012). Ezeokonkwo and Dodson (2004) reported that the seed has essential amino acids that can support growth and a high dietary protein quality.…”
Section: Introductionmentioning
confidence: 58%
“…It was introduced to Brazil, the Caribbean, and East Africa for shade and ornamental purposes in urban and rural afforestation and reforestation (Gilman and Watson 1994;Oliveira et al 2000; Thomson and Evans 2006;Ezeokonkwo 2000). The flowering season occurs between April-May and September-October while its fruiting season is from October to April (Salvo et al 1983).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations